Characteristics of general practices associated with emergency admission rates to hospital: a cross-sectional study. Issue 7 (22nd April 2011) - Bankart, M J G; Baker, R; Rashid, A; Habiba, M; Banerjee, J; Hsu, R; Conroy, S; Agarwal, S; Wilson, A
Abstract : Objectives: To identify characteristics of general practices associated with emergency hospital admission rates, and determine whether levels of performance and patient reports of access are associated with admission rates. Design: A cross-sectional study. Setting: Two primary care trusts (Leicester City and Leicestershire County and Rutland) in the East Midlands of England. Participants: 145 general practices. Methods: Hospital admission data were used to calculate the rate of emergency admissions from 145 practices, for two consecutive years (2006/7 and 2007/8). Practice characteristics (size, distance from principal hospital, quality and outcomes framework performance data, patient reports of access to their practices) and patient characteristics (deprivation, ethnicity, gender and age), were used as predictors in a two-level hierarchical model, developed with data for 2007/8, and evaluated against data for 2006/7. Results: Practice characteristics (shorter distance from hospital, smaller list size) and patient characteristics (higher proportion of older people, white ethnicity, increasing deprivation, female gender) were associated with higher admission rates. There was no association with quality and outcomes framework domains (clinical or organisation), but there was an association between patients reporting being able to see a particular general practitioner (GP) and admission rates. As the proportion of patients able to consult a particular GP increased, emergency admission rates declined. Conclusions: The patient characteristics of deprivation, age, ethnicity and gender are important predictors of admission rates. Larger practices and greater distance from a hospital have lower admission rates. Being able to consult a particular GP, an aspect of continuity, is associated with lower emergency admission rates.